Biallelic mutations in LSS in autosomal‐recessive mutilating palmoplantar keratoderma. Issue 5 (6th March 2023) - Zhou, Shengru; Jiang, Xingyuan; Zhu, Yuhao; Yang, Jianqiu; Yuan, Chunyu; Chen, Min; Zhou, Qianqian; Lin, Zhimiao; Li, Min
Abstract: Mutilating palmoplantar keratoderma (PPK) is a heterogeneous genetic disease that poses enormous challenges to clinical diagnosis and genetic counselling. Lanosterol synthase ( LSS ) gene encodes LSS involved in the biosynthesis pathway of cholesterol. Biallelic mutations in LSS were found to be related to diseases such as cataracts, hypotrichosis and palmoplantar keratoderma‐congenital alopecia syndrome. The aim of this study was to investigate the contribution of the LSS mutation to mutilating PPK in a Chinese patient. The clinical and molecular characteristics of the patient were evaluated. A 38‐year‐old male patient with mutilating PPK was recruited in this study. We identified biallelic variants in the LSS gene (c.683C > T, p.Thr228Ile and c.779G > A, p.Arg260His). Immunoblotting revealed that the Arg260His mutant showed a significantly reduced expression level while Thr228Ile showed an expression level similar to that of the wild type. Thin layer chromatography revealed that mutant Thr228Ile retained partial enzymatic activity and mutant Arg260His did not show any catalytic activity. Our findings show the correlation between LSS mutations and mutilating PPK.